AB0594 EFFECTIVENESS OF RITUXIMAB IN CSDMARDS-RESISTANT ACTIVE MIXED CONNECTIVE TISSUE DISEASE. (2nd June 2020) - Montolio-Chiva, L.; Narváez, J.; Alegre-Sancho, J. J.; Lluch Pons, J.; Orenes Vera, A. V.; Vázquez-Gómez, I.; Mora, M.; González, X.; Marco, C.; Rodriguez, J.; Romera, M.; Nolla, J. M.
Abstract : Background: Objectives: To evaluate rituximab (RTX) effectiveness and safety in treating patients with refractory mixed connective tissue disease (MCTD). Methods: Open observational study including patients with refractory MCTD (active disease despite treatment with glucocorticoids and csDMARDs) from two third-level hospitals who had been treated with RTX (off-label use) from January 2001 to December 2019. Results: Thirteen patients (all women) were included, with a mean age of 32 years (SD: 10, range 17-50) and a median time of evolution of the disease of 55 months (SD: 34.3; range 5-98 months). The main indication for initiating treatment with RTX was refractory arthritis (100%), most of the times accompanied by other features of the disease including shrinking lung syndrome (2), fibrosing progressive non-specific interstitial pneumonia (FP-NSIP) (1), recurrent serositis (2), glomerulonephritis (GMN) (2), lymphadenitis (1) and immune thrombocytopenic purpura (ITP) (1). All patients were treated with RTX at rheumatoid arthritis dosage while the baseline immunosuppressive treatment (methotrexate, azathioprine, mycophenolate, leflunomide or tacrolimus) remained unchanged. Hydroxychloroquine was also associated in 8 of the patients. The follow-up time (median) after starting RTX was 118 months (range, 65-177 months, with a total of 132.6 patient-years of follow-up) and the mean number of cycles of treatment was 4.2 (range, 1-15), with a variable interval (from 6 to 12 months). After the first RTX cycle, a partial or complete response was achieved in 92% of the patients. A significant improvement in the mean DAS28-ESR was observed (initial: 4.56 ± 1.6 / final: 2.21 ± 0.85; p=0.008). In all but one patient, who had previously failed to 2 anti-TNFα DAS28-ESR clinical remission or low activity was achieved, generally from week 16 to 20, although relapses were frequent and all cases need retreatment after 6-9 months. In 4 patients, RTX retreatment dosage was optimized to 1 g/cycle. The 3 patients with pulmonary involvement showed stabilization (2 cases) or improvement (1) of the lung function (as defined by the American Thoracic Society ). In patients with GMN, renal response to RTX treatment was complete in a patient and partial in the other. The patient with ITP entered remission after the first RTX cycle and no more cycles were needed. Response in patients with serositis and lymphadenitis was also complete and maintained. Moreover, the glucocorticoid doses were reduced to less than half of the initial dose in all cases. At the end of the follow-up, 7 out of the 13 patients (54%) were still being treated with RTX. For the remaining 6 patients, RTX was withdrawn because of primary failure (1), recurrent bacterial infections (2), gestational desire (2) sustained remission (1). Conclusion: According to our preliminary results, RTX seems to be effective and relatively safe in patients with csDMARDs-resistant active MCTD. Disclosure of Interests: L Montolio-Chiva: None declared, J. Narváez: None declared, Juanjo J Alegre-Sancho Consultant of: UCB, Roche, Sanofi, Boehringer, Celltrion, Paid instructor for: GSK, Speakers bureau: MSD, GSK, Lilly, Sanofi, Roche, UCB, Actelion, Pfizer, Abbvie, Novartis, J Lluch Pons: None declared, Ana V Orenes Vera: None declared, I Vázquez-Gómez: None declared, Maribel Mora: None declared, Xavier González: None declared, Carla Marco: None declared, Jesús Rodriguez: None declared, Montserrat Romera: None declared, Joan Miquel Nolla: None declared